Implementasi Data Mining Untuk Pengembangan Sistem Rekomendasi Pemilihan SMK Dengan Menggunakan Algoritma Cart - Ade Septi Binjori (STMIK Budi Darma, 2020)
Recommendation for choosing a Vocational High School (SMK) is a procedure that is carried out to provide supporting information for students graduating from SMP or MTS in the selection of Vocational High Schools (SMK) for advanced junior high school or MTS education to Vocational High School (SMK) education. Most countries have formal education systems that are usually needed. Every year, students will look for schools. Problems arise and contain many choices that provide a variety of offers and choices to prospective students. Therefore we need a system that not only provides information about schools, and also is not able to contribute to the appropriate school of each prospective student.The decision tree that produces CART is a binary tree that has attribute values by selecting the most optimal branching in each variable. The principle of the clafication tree is to separate all observations into two observation groups into the next two observation groups, that is, the minimum number of tantrums when the observation group.